IMPLEMENTASI METODE PEMBELAJARAN BELAJAR SAMBIL BERNYANYI DALAM MENUMBUHKEMBANGKAN PENDIDIKAN KARAKTER ANAK DI PAUD HINDU DAMA KUMARA DESA PATEMON KABUPATEN BULELENG (KAJIAN ETNOPEDAGOGI) - Komang Sudarsana; I Gede Suwindia; I Wayan Gata (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2022)
The learning while singing method can also be referred to as a method of modifying several methods in it such as lecture methods, modeling, experiments, demonstrations by prioritizing memory skills, courage, Hindu religious material such as an introduction to the Vedic scriptures, holy places, holy people, holy days, introduction teachings of Tri Hita Karana, Tri Kaya Parisudha, Panca Sradha and so on. The values of the teachings of Hinduism are integrated into the singing method, where while singing children are actually learning to know and understand the teachings of Hinduism. So that by itself it will be able to develop the character of the child for the better. The results of the study show that (1) Establish a method of learning while singing in developing character education for students, namely singing, singing along with applause, movement, or musical accompaniment. Through singing activities, children can get to know rhythm, understand a concept according to the content of the lyrics, express themselves, and much more. (2) The stages of implementing the learning while singing method, the teacher first knows clearly the content of the material to be conveyed and puts it into the song lyrics, chooses a song tone that is familiar to students, the teacher introduces the song and explains the meaning contained therein, demonstrates together -same and repeated accompanied by appropriate body movements. (3) The implications are very positive, it is known from the responses of the principal, teachers, students and parents of students that there is comfort in the learning process that is applied, there are changes in attitudes and behavior of students and the responses of parents who are enthusiastic about sending their children to PAUD Hindu Dama Kumara Patemon Village.Keywords: Implementation, Singing Learning Learning Method, Developing Character Education, Ethnopedagogy